Sweat conductivity test: can it replace chloride titration for cystic fibrosis diagnosis? - Cinel, Güzin; Doğru, Deniz; Yalçın, Ebru; Özçelik, Uğur; Gürcan, Nermin; Kiper, Nural (The Turkish Journal of Pediatrics, 2012)
Although sweat conductivity values are well matched with chloride concentrations for cystic fibrosis (CF) diagnosis, sweat conductivity is not accepted as a definitive diagnostic tool but only a screening method. The aim of this study was to compare the sweat chloride measurements and sweat conductivity values of our patients, and to determine cut-off values of conductivity for making or excluding a CF diagnosis. Fifty-nine CF patients, 10 patients with elevated sweat tests and 69 non-CF patients were included in the study. The mean conductivity values were 123 (64-157) mmol/L, 75.1 (60-93) mmol/L and 39 (18-83) mmol/L in the CF, elevated sweat test and control groups, respectively. The mean chloride concentration values were 107.5 (35-166) mEq/L, 48 (42-76) mEq/L and 25 (11-39) mEq/L in the CF, elevated sweat test and control groups, respectively. Spearman correlation test determined a strong correlation between conductivity and chloride concentration values (r=88%, p